2012
DOI: 10.1186/1687-6180-2012-168
|View full text |Cite
|
Sign up to set email alerts
|

Extending the scope of empirical mode decomposition by smoothing

Abstract: This article considers extending the scope of the empirical mode decomposition (EMD) method. The extension is aimed at noisy data and irregularly spaced data, which is necessary for widespread applicability of EMD. The proposed algorithm, called statistical EMD (SEMD), uses a smoothing technique instead of an interpolation when constructing upper and lower envelopes. Using SEMD, we discuss how to identify non-informative fluctuations such as noise, outliers, and ultra-high frequency components from the signal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…It is worthy of mention that this method is different than some works with a similar names reported in [44,45,46,47]. …”
Section: Smooth Empirical Mode Decomposition (Semd)mentioning
confidence: 90%
“…It is worthy of mention that this method is different than some works with a similar names reported in [44,45,46,47]. …”
Section: Smooth Empirical Mode Decomposition (Semd)mentioning
confidence: 90%
“…Wu and Huang [18] developed the ensemble EMD (EEMD) by averaging out the noise from the simulated signals. Kim et al [19] introduced the statistical EMD that uses smoothing of local extrema instead of interpolation. More recently, Komaty et al [20] suggested a signal-filtering approach based on a combination of EMD and a similarity measure for noise removal.…”
Section: Outlinementioning
confidence: 99%
“…It represents a signal by a linear combination of wavelet basis functions. Its decomposition results for nonlinear data can be misleading (Huang and Wu, 2008;Kim et al, 2012). Furthermore, wavelet analysis suffers from its nonadaptive nature as it applies the same type of basis functions to the entire range of data.…”
Section: Introductionmentioning
confidence: 99%